Effect of Testosterone Administration and Spiking on Reproductive Success of Broiler Breeder Flocks. Issue 5 (19th August 2015) - Ordas, B; Vahedi, S; Seidavi, A; Rahati, M; Laudadio, V; Tufarelli, V
Contents: Age negatively affects reproductive success of broiler breeder flocks. One of the main hormones involved in the change of fertility with the age is testosterone (TT). The introduction of young males at later production stages of broiler flocks is known as spiking and is expected to reduce the fertility decline with age. The aim of this study was to determine the effect of injection of different levels of TT and the effect of spiking on reproductive fitness of broiler breeder flocks. Two experiments were conducted on Ross 308 breeder flocks for 10 weeks (41–50 weeks of age). The experiment 1 included a control and three treatments corresponding to three doses of TT (0.1, 0.2 and 0.3 cc), while the experiment 2 included a control and one treatment corresponding to spiking. The lower dose of TT (0.1 cc) and the spiking clearly slowed down the decline in hatchability. Therefore, either the external administration of TT to the males when the natural concentration of TT starts to decline or spiking the breeder flock with young roosters could contribute to improve reproductive success in later stages of the production cycle in broiler breeder flocks.